Analysis of the cause of loss of PT. Asuransi Jiwasraya (Persero) - Girang Permata Gusti (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2019)
Research purposes – to analyse the causes of losses faced by PT. Asuransi Jiwasraya and review in more detail, what are the factors of the cause of the financial problems faced by Jiwasraya, so that the company has stood for 160 years With assets in the year 2017 of 45 trillion rupiah, a sudden loss of 13 trillion rupiah with a debt of 49 trillion rupiah in 2019.Design / Methodology / Approach – This research uses descriptive research method, which aims to explain a phenomenon or event systematically and as it is, this research was conducted to obtain information about the previous situation and the current situation to be analyzed so that the core of the problem that causes the research can be found. This study uses a case study model that occurred at PT. Asuransi Jiwasraya, which is experiencing financial problems due to mismanagement and misplacement of customers 'investment funds, has caused it to be unable to return investment funds and pay customers' investment interest.Finding – (1) Management's mistake in placing the customer's investment fund is the main cause of insurance payment to the customer. (2) JS Saving is a not unit link investment where the risk is entirely borne by the insurance company. The lure of a High Return JS Saving Plan is offered with a guaranteed return of 9 percent to 13 percent from 2013 to 2018 with a disbursement period every year. (3) Jiwasraya manipulates its financial statements so that they can look good to investors. (4) Management is too aggressive in investing to pursue the company's profit targets and target payment obligations to all customers who buy investment products.Research limitations – This research is limited to cases that occur in the insurance company Jiwasraya, with no comparison with other insurance companies or other investment companies.Originality/value – The authenticity of the analysis and observation to obtain valid and accountable data, the results are used to find the main cause of the losses that occur at the insurance company under study. Keywords: Jiwasraya Insurance; Stock Investment; Mismanagement